Impulsive actions and choices in laboratory animals and humans: effects of high vs. low dopamine states produced by systemic treatments given to neurologically intact subjects - D’Amour-Horvat, Valérie; Leyton, Marco (Frontiers in Behavioral Neuroscience, 2014)
Increases and decreases in dopamine transmission have both been suggested to influence reward-related impulse-control. The present literature review suggests that, in laboratory animals, the systemic administration of dopamine augmenters preferentially increases susceptibility to premature responding; with continued dopamine transmission, reward approach behaviors are sustained. Decreases in dopamine transmission, in comparison, diminish the appeal of distal and difficult to obtain rewards, thereby increasing susceptibility to temporal discounting and other forms of impulsive choice. The evidence available in humans is not incompatible with this model but is less extensive.